Uma geologia cartográfica da experiência psicodélica - Puzzi, Ricardo Fabiano (2024)
Psychedelics are substances, mostly derived from plants that occupy psychoactive floras around the world. Despite being present since the beginning of the human relationship with plants and drugs, they gained prominence from the end of the 19th century and beginning of the 20th century as part of the study of modern pharmacology and resurfaced through the Psychedelic Renaissance after the rise of prohibitionism through new clinical trials. Considering all the territorial and ecological issues regarding the use of drugs and plants, this dissertation aims to expand and problematize the understanding of the experience with psychedelics in a transversal and dynamic way through the cartographic method. In the meantime, we seek to approach schizoanalytic concepts such as territoriality, agency and machinic animism. The intention is to form a plane of consistency about the psychedelic experience. We then have, as a result, a problematization of the social strata surrounding the entire territorial range of this experience. The main criticism produced here highlights the occupation with the psychedelic experience as an event that calls for new readings beyond the capture of capitalist states that subverted our ecological relationship with plants and drugs. The issues of biopolitics, necropolitics and the idealization of a gold standard of pharmacology as an idea of ​​mental health as a homeostatic appeasement of anguish are also taken into consideration. While the recovery of knowledge about psychedelics from indigenous peoples such as Amerindian perspectivism is also promoted. It is concluded that there is a diversity of possible adult uses beyond the idea of ​​recreational and therapeutic use. The use of psychedelics in a quality capable of promoting or not lines of escape for rigid social strata.